2013
DOI: 10.7897/2230-8407.04549
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Methanolic Extract of the Shoot of Plectranthus Hadiensis

Abstract: The herbal renaissance has been taking place throughout the world over the last few years. Over the period, herbal medicines have moved from an empirical basis to its present as an increasingly scientifically based system of healing, being referred as phytotherapy. Although the traditional medicinal systems adopt a holistic approach while using herbs or their combinations, knowledge of individual constituents facilitates in developing quality control methods, extraction procedures, understanding of pharmacolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…Concerning its phytochemical analysis and biological activity, polyphenols, alkaloids, tannins, cardiac glycosides, saponins, and terpenoids have been identified in different parts, such as roots, stems, leaves, and whole extracts [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Although some of these compounds have been isolated, the phytochemistry of this genus is far from being fully known [31].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Concerning its phytochemical analysis and biological activity, polyphenols, alkaloids, tannins, cardiac glycosides, saponins, and terpenoids have been identified in different parts, such as roots, stems, leaves, and whole extracts [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]. Although some of these compounds have been isolated, the phytochemistry of this genus is far from being fully known [31].…”
Section: Introductionmentioning
confidence: 99%
“…Other studies reported on its anti-inflammatory activity (inhibiting cyclooxygenases 1 and 2 (COX-1, COX-2) and lipoxygenases 2 and 15 (LOX-2, LOX-15) [17,31,36]. It also exerts antioxidant [20][21][22]24,32,36], larvicidal [18], insecticidal [23], and antiplasmodial activities [25,27], and is used to treat sore throat, fever, and nauseas [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The top genera medicinal orchids are Dendrobium (23 species), Calanthe (7 species), Liparis (6 species), Bulbophyllum, Cymbidium, Eulophia, Habenaria, Phaius (each 4 species) and Coelogyne, Phalaenopsis, Vanilla (each with 3 species). Genera of Calanthe, Coelogyne, Cymbidium, and Dendrobium [3] and Vanilla are among the medicinal orchid [21].…”
Section: Resultsmentioning
confidence: 99%
“…A leaf extract displayed low larvicidal activity against the fourth instar larvae of Aedes aegypti , a dengue fever vector (LC 50 : 489.278 µ g/mL) [ 112 ]. A terpene-rich methanolic extract of the shoot part and a methanolic extract of the stem was investigated for cytotoxicity using a shrimp brine lethality assay (LC 50 : 145 µ g/mL) and against HeLa cells (141.3 μ g/mL) [ 113 , 114 ]. Other studies include (a) antibacterial susceptibility single dose and antioxidant activity studies [ 115 117 ]; (b) two studies investigating the antioxidant, antiproliferative, and antiinflammatory properties of the shoot parts [ 118 , 119 ]; and (c) a study screening several Plectranthus species, including P. hadiensis , for antiinflammatory effects [ 120 ].…”
Section: Resultsmentioning
confidence: 99%